INTERCULTURAL COMPETENCE AS A SCIENTIFIC CATEGORY: NATIONAL AND GLOBAL APPROACHES TO RESEARCH - Semeniuk, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The article is dedicated to the topical problem of defining intercultural competence and the analysis of existing approaches in national and global practice. The aim of the work is the analysis of the concept of “intercultural competence”, the disclosure of its content in Ukrainian and foreign studies, clarification of the main features as well. In accordance with the aim, the following tasks were solved: to analyse scientific approaches to the definition of the concept of “intercultural competence” in Ukrainian and foreign scientific sources; to reveal the influence of the internationalization and globalization processes in the system of higher education of Ukraine on the formation of intercultural competence; to clarify the main characteristics of intercultural competence. The following methods were used: analysis, comparison, generalization, systematization. It has been established that in national approaches to the study of intercultural competence, it is preferable to consider it in the context of professional education. The article also pays considerable attention to the peculiarities of approaches to the study of the concept of “intercultural competence” in foreign research, it is emphasized that such approaches are more generalized due to the fact that foreign students have been studying and solving various issues related to the formation of their intercultural competence in many countries for a long time. Such approaches are observed in the research of Canadian scientists, as well as in the materials of the international organization UNESCO, which combines the experience and scientific assets of scientists from different countries. The article draws attention to the fact that intercultural competence is an important component of educational programs in foreign educational systems. The main characteristics of the content of the concept of “intercultural competence” are presented, as well as its main features are analysed and systematized, among which we can name: the dynamic and complex nature of intercultural competence, its orientation to the result, reflection in action, orientation to a certain area of human activity. The content of the indicated characteristics is outlined. The practical significance of the article is that its materials can be used to prepare students who will work in an international environment in the future, negotiate and participate in international projects, resolve conflicts, act wisely within the framework of intercultural interaction, based on existing approaches to defining intercultural competence in Ukraine and abroad.